Florida's Introduced Birds: Sacred Ibis (Threskiornis aethiopicus) - Steven A. Johnson; Monica McGarrity (EDIS, 2009)
WEC-267, a 7-page illustrated fact sheet by Steve Johnson and Monica McGarrity, describes this larger black-necked relative of Florida’s native ibises — species description, similar species, native range and habitats, mode of introduction, introduced range and habitats, ecology, ecological impacts, impacts on people and pets, solutions, and how you can help. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, October 2009.